The Persistence of Faith: Changes and Validity of Political-Religious Cleavage in Chile (1938-2017) [Persistência Da Fé: Mutações y Validade Da Clivagem Político-Religiosa No Chile (1938-2017)] [la Persistencia de la Fe: Cambios y Vigencia del Clivaje Político-Religioso en Chile (1938-2017)] - Elgueta-Rosas, R; Fediakova, E; Santoni, A (Editora da P U C R S, 2019)
This article analyzes how religious cleavage has influenced on the structuring of the Chilean political system in different moments of its democratic life: from the victory of the Popular Front in 1938 to the coup d’état of 1973, to which followed the return to democracy in 1990. It suggests that, in spite of secularization and growing number of agnostics, religion has not lost its validity in the public sphere, inspiring the creation of different parties and producing changes in identities and agendas. Religious cleavage has changed its meaning, constantly interacting with other dimensions of ideological competency. As for the catholic field, the process has been beneficial for different groups at different stages, insofar as it expresses a variety of contending interpretations of the public role of faith. At the same time, there is a growing evangelical field and its quest to enter the public arena makes this case more complex, producing new challenges and political alignments. © 2019, Editora da P U C R S. All rights reserved.